Why Blame? - Gurdal, Mehmet Y.; Miller, Joshua B.; Rustichini, Aldo (Journal of Political Economy, 2013)
We provide experimental evidence that subjects blame others on the basis of events they are not responsible for. In our experiment an agent chooses between a lottery and a safe asset; payment from the chosen option goes to a principal, who then decides how much to allocate between the agent and a third party. We observe widespread blame: regardless of their choice, agents are blamed by principals for the outcome of the lottery, an event they are not responsible for. We provide an explanation of this apparently irrational behavior with a delegated-expertise principal-agent model, the subjects’ salient perturbation of the environment.